2020
DOI: 10.1002/ccd.28758
|View full text |Cite
|
Sign up to set email alerts
|

Slender versus conventional approach reduces post‐procedural upper extremity dysfunction after transradial coronary procedures

Abstract: AimsWe compared the incidence of post‐procedural radial artery occlusion (RAO) and upper extremity dysfunction (UED), in patients undergoing conventional versus slender transradial (TRA) coronary procedures.Methods and resultsUED was assessed by the QuickDASH, before conventional (i.e., ≥6F) and slender (i.e., “virtual” 3F to 5F) procedures, after 2 weeks and 2 months. RAO was assessed by Duplex in patients with an abnormal reversed Barbeau test (RBT). A total of 212 patients were included, UED after 2 weeks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Reducing catheter size from 6F to 5 French (5F) slender and sheathless techniques might reduce incidence of complications, especially in women and older age groups. 18,[25][26][27] One study confirmed that in comparison with a 6F sheath, 20% more women and 10% more men complied with a sheath-to-artery ratio of less than 1 when using a 5F sheath. 27 Radial arteries with smaller diameter may cause more spasm due to catheter friction.…”
Section: Discussionmentioning
confidence: 96%
“…Reducing catheter size from 6F to 5 French (5F) slender and sheathless techniques might reduce incidence of complications, especially in women and older age groups. 18,[25][26][27] One study confirmed that in comparison with a 6F sheath, 20% more women and 10% more men complied with a sheath-to-artery ratio of less than 1 when using a 5F sheath. 27 Radial arteries with smaller diameter may cause more spasm due to catheter friction.…”
Section: Discussionmentioning
confidence: 96%
“…9 The QuickDASH has been used to assess the upper extremity function following TR-PCI. [10][11][12] The use of these patient-reported outcome measures (PROMs), however, has not yet been validated for TR-PCI induced complications in the upper extremity. The objective of this analysis was to establish the validity of the DASH and QuickDASH questionnaires for the assessment of upper extremity dysfunction (UED) following TR-PCI.…”
Section: Introductionmentioning
confidence: 99%